Pemikiran Imam Al-Syafi'i mengenai Sadd Al-Dhara`i' sebagai Sumber Hukum - Wan Hassan, Wan Zulkifli bin; Hj Abdullah, Luqman; Man, Saadan (Jurnal Fiqh, 2008)
The doctrine of Sadd al-Dhara`i' (Blocking the Means) in Usul al-Fiqh generally means preventing bad thing before it comes to materialize. The Muslim scholars are in disagreement over the validity of Sadd al-Dhara`i' as a source of Islamic law. Imam al-Syafi'i was said to have excluded it in his listing to the sources of Islamic law. However, a thorough study and observation suggest that he used to apply Sadd al-Dhara`i' in many of his juristic opinions though on an indirect basis. This article will explore this isue so as to give a clear picture the position of Imam al-Syafi'i regarding Sadd al-Dhara`i'.